Activity-directed expansion of a series of antibacterial agents. Issue 58 (15th June 2020) - Leggott, Abbie; Clarke, Justin E.; Chow, Shiao; Warriner, Stuart L.; O'Neill, Alex J.; Nelson, Adam
Abstract : Activity-directed synthesis harnessing 220 Pd-catalysed microscale reactions enabled expansion of a series of quinazolinone antibacterials. Abstract : The feasibility of using activity-directed synthesis to drive antibacterial discovery was investigated. An array of 220 Pd-catalysed microscale reactions was executed, and the crude product mixtures were evaluated for activity against Staphylococcus aureus. Scale-up of the hit reactions, purification and evaluation, enabled expansion of a class of antibacterial quinazolinones. The novel antibacterials had MICs from 0.016 μg mL −1 ( i.e. 38 nM) to 2–4 μg mL −1 against S. aureus ATCC29213.